Towards a low-carbon footprint: Current status and prospects for aquaculture - Zhimin Zhang; Haokun Liu; Junyan Jin; Xiaoming Zhu; Dong Han; Shouqi Xie (Water Biology and Security)
Aquaculture is one of the fastest-growing agricultural sectors globally and is becoming increasingly important for producing sustainable and healthy diets with relatively low climate impacts. In comparison to livestock production, especially beef, seafood production has lower carbon emissions. Additionally, some species can extract carbon from aquatic environments, contributing to an extended carbon cycle. However, the potential for negative environmental consequences in aquaculture production might increase with the growing global population and demand for aquatic food. Herein, we review the environmental consequences of aquaculture production and the potential effects of different aquatic products on greenhouse gas (GHG) emissions. We also summarize approaches to improving environmental footprints for mitigating global climate change. Key elements, including improving feed efficiency, selecting suitable farmed species, and implementing sustainable farming practices and management in aquaculture, are discussed, as well as the trade-offs between aquaculture and capture fisheries. Crucially, performance gaps among farmed species underscore the potential for consumer-oriented advice to significantly reduce the effects of aquaculture on climate change. However, uncertainties and knowledge gaps related to carbon sequestration and GHG emissions in aquaculture ponds necessitate further research. Overall, holistic evaluation and strategic intervention regarding GHG emissions are fundamental and essential for achieving a sustainable, low-carbon future for aquaculture.